Enhancing the recognition of tumour associated antigens - Restifo, N P; Minev, B R; Taggarse, A S; McFarland, B J; Wang, M; Irvine, K R (Folia biologica, 1994)
Activated CD8+ T cells (TCD8+) can directly recognize malignant cells because processed fragments of tumour associated antigens (TAA), 8-10 amino acids in length and complexed with MHC class I molecules, are displayed on tumour cell surfaces. Tumour cells have been genetically modified in a variety of ways in efforts to enhance the immune recognition of TAA. An alternative strategy is the expression of TAA in recombinant or synthetic form. This has been made possible by the recent cloning of TAA recognized by TCD8+. In this communication we review recent work in our own laboratory on the expression of TAA as synthetic peptide, by "naked" plasmid DNA injected intramuscularly or transdermally, and by recombinant viruses including vaccinia (rVV), fowlpox (rFV) and adenovirus (rAd). The expression of TAA in recombinant and synthetic forms allows increased control over the quantity, location, and kinetics of TAA presentation and can result in powerful, specific, anti-tumour immune responses.
Keywords: interferon gama; Molecular Sequence Data; Interferon-gamma; prezentace antigenu; sekvence aminokyselin; Oligopeptides; Antigen Presentation; Gene Expression Regulation, Viral; rekombinantní proteiny; oligopeptidy; Mice; regulace exprese virových genů; CD8-pozitivní T-lymfocyty; Antigens, Neoplasm; imunoterapie; zvířata; Amino Acid Sequence; myši; Immunotherapy; antigeny nádorové; molekulární sekvence - údaje; CD8-Positive T-Lymphocytes; Recombinant Proteins; Animals